Central bank tenders: Three essays on money market liquidity auctions - Tuomas Välimäki (Bank of Finland, 2003)
Most OECD central banks implement monetary policy by supplying reserves to the banking sector with the aim of influencing short-term interbank interest rates.To interpret the monetary policy stance accurately, one needs to be familiar with the mechanism for determining the money market equilibrium.The aim of this study is to deepen our understanding of the various effects of different intervention styles on the short-term money market when monetary policy is implemented with an operational framework similar to that of the European Central Bank (ECB).In the first essay of this study, we model banks' demand for central bank reserves (liquidity) for each day of an n-day reserve maintenance period and analyse liquidity determination under alternative liquidity policy rules that a central bank might apply in fixed rate tenders.It is shown that there is a tradeoff between the central bank's ability to keep a market interest rate close to the tender rate and the stability of liquidity holdings within a maintenance period.The second essay presents a model of a single bank's optimal bidding in the context of fixed rate liquidity tenders.It is shown that banks' bidding crucially depends on the central bank's liquidity policy for tender allotments. This essay also analyses ECB liquidity policy in terms of the model.The final essay models the money market equilibrium and analyses Banks' bidding when the central bank uses variable rate tenders.The liquidity supply is fully endogenised by having the central bank minimise a loss function the includes deviations-from-target of interest rate and liquidity.ECB experiences with variable rate tenders are also studied in this essay.
URN:NBN:fi:bof-201408071678
Keywords: 330; central bank operational framework; short-term interest rates; money markets; tenders; liquidity policy; bidding.